Circularly polarized dielectric resonator‐based multiple input multiple output antenna with pattern and polarization diversity for vehicular applications. (8th June 2021) - Srivastava, Komal; Dwivedi, Ajay Kumar; Sharma, Anand
Summary: In this article, a modified layout of cylindrical dielectric material‐based, resonator‐type multiple input multiple output antenna (MIMO) is presented. The beam tilting feature is achieved by using a conducting plate placed in the mid of two antenna elements. Dual frequency‐band operation, that is, 2.4–4.02 and 4.78–6.21 GHz is obtained by sourcing the ring DRA electromagnetically with asymmetric S‐shaped aperture via microstrip line. Dual CP waves are supported by the designed antenna within the operating frequency band, that is, 2.84–2.95 and 5.63–5.66 GHz. The two ports are placed in parallel. Some salient features of the designed antenna are (i) pattern diversity ( θ = ±30° in XZ plane) is obtained between two parallel placed ports by applying conducting plate; (ii) polarization diversity is obtained by simply taking a mirror image of the proposed aperture. The most favorable value of diversity parameters of the suggested DR‐based MIMO antenna makes it satisfactory for smart transport and vehicular communication applications in the sub‐6‐GHz range. Abstract : In this multiple input multiple output antenna (MIMO) structure, the beam tilting feature is achieved by using a conducting plate placed in the mid of two elements. Dual‐band operation, that is, 2.4–4.02 and 4.78–6.21 GHz is obtained by sourcing the ring DRA with asymmetric S‐shaped aperture via microstrip line. Its features are suitable for the sub‐6‐GHz range.